Granulocyte-Monocyte Apheresis in Steroid-Dependent, Azathioprine-Intolerant/Resistant Moderate Ulcerative Colitis: A Prospective Multicenter Study - Gianni Imperiali; Arnaldo Amato; Maria Maddalena Terpin; Ivo Beverina; Aurora Bortoli; Massimo Devani; Chiara Viganò; Study Group on IBD (GSMII) (Gastroenterology Research and Practice)
Background. Granulocyte-monocyte apheresis has been proposed for the treatment of ulcerative colitis, although it is limited by costs and variability of results. Aim. To assess effectiveness of granulocyte-monocyte apheresis in patients with steroid-dependent, azathioprine-intolerant/resistant moderate ulcerative colitis. Methods. Consecutive patients fulfilling inclusion criteria were prospectively enrolled, treated by apheresis, and followed up for 12 months. The primary end point of the study was steroid-free clinical remission at 12 months, with no need for biologic therapy or surgery. Results. From January to December 2013, 33 patients were enrolled. After one year of follow-up, 12 (36%) patients had clinical remission, were steroid-free, and had no need for biological therapy or surgery; 3 (9%) cases showed a clinical response (but not clinical remission). Moreover, 12 (36%) patients required biologic therapy, 4 (12%) underwent colectomy, and in the other 2 (6%) a reduction, but not withdrawal, of steroid dose was achieved. Conclusions. Our study shows that a standard course of granulocyte-monocyte apheresis is associated with a 36% steroid-free clinical remission in patients with steroid-dependent, azathioprine-intolerant or resistant moderate ulcerative colitis. Apheresis might represent an alternative to biologic therapy or surgery in this specific subgroup of patients. This trial is registered with Clinicaltrial.gov NCT03189888.